Performance of SAC-OCDMA codes for multipoint fiber vibration sensing - Danjuma, Kuje; Taiwo, Ambali; Sahbudin, Ratna Kalos Zakiah; Mokhtar, Makhfudzah; Yaacob, Mohd. Hanif (IEEE (IEEE Xplore), 2014)
Performance of Spectral Amplitude Coding - Optical Code Division Multiple Access (SACOCDMA) based fiber vibration sensor multiplexing using Multi-Service (MS) code has been investigated. The aim of the setup was to implement a multipoint fiber vibration sensing with less complexity, efficient performance against multiple access interference (MAI) and phase induced intensity noise (PIIN) which degrade performances. Comparison was made of the three sensing points with other existing SAC codes such as the Khazani Syed (KS) code, Modified Congruence Code (MQC) and Optical Orthogonal Code (OOC) in terms of level of signal power received, fiber length supported and complexity of system implementation. MS code has advantage of better received power hence supported longer fiber length, flexibility in increasing the number of sensors, service differentiation and shorter code length. Moreover, it has some close chips which can be filtered using single FBG therefore reduces the cost and complexity in sensor multiplexing.